SNA: IBM's networking solution - Martin, James (Prentice-Hall Englewood CliffsUS, 1987)
Presents a detailed explanation of concepts, protocols, functions, and capabilities that constitute SNA (Systems Network Architecture) as an architecture. Points out need for hardware compatibility as increasingly complex computer networks proliferate. Describes several classes of SNA compatible hardware and software products and provides context within which the capabilities, functions and operations of specific products can be understood. Discusses IBM's SNA in detail focusing on path control network; transmission and data flow control and function management.